Digital banking's effect on the banking industry & system transformation - Sarker, Debobrota Kumar; Sarker, Bipul Kumar; Shaha, Shompa Rani; Sarker, Sajib; Borddin, Ali (Annals of Management and Organization Research, 2025)
Purpose: This study examines how digital banking has affected Bangladesh's banking industry by emphasizing its ramifications, difficulties, and revolutionary influences. Research Methodology: With 200 participants and secondary sources, this study employs a mixed-methods approach and concludes that digital banking improves financial inclusion, convenience, and security.  However, obstacles to complete adoption include societal problems, legislative restrictions, and inadequate infrastructure.  While inequalities in digital literacy and geographic access continue to be major concerns, security, accessibility, and time efficiency are also important contributing variables. Results: Although the results highlight the potential of digital banking to modernize the banking sector and promote economic growth, their wider application is limited by factors, including their geographical concentration and dependence on self-reported data. Conclusions: Bangladesh has enormous potential for equitable growth and financial innovation compared with digital banking. Nevertheless, for widespread adoption, infrastructure deficiencies, digital illiteracy, and security issues must be addressed. Limitations: This study's limitations include its dependence on self-reported data, regional focus, and inadequate technology infrastructure that affects the uptake of digital banking. Contribution:  This study advances our knowledge of how digital banking is changing conventional banking institutions and provides practical advice to industry executives and legislators on how to remove obstacles and create a more robust and inclusive financial system. Novelty: This study emphasizes financial inclusion, technological obstacles, and specific recommendations for sustainable growth and innovation, highlighting the revolutionary influence of digital banking on Bangladesh's banking industry.